Cultura, identidade e surdez: contribuições teóricas a partir de uma abordagem interdisciplinar - SILVA, Maria Benedita Gomes da (2019)
This paper presents a discussion of the deaf identification processes in their interface with culture. To reflect on the factors, that possibly, influence to the deaf identity, it was decided to develop an interdisciplinary approach, with emphasis in the areas of Psychoanalysis and Anthropology. In psychoanalytic theoretical strand, specifically about the broader understanding of culture, we used from Sigmund Freud, the "Mal Estar na Civilização"; and to discuss the general aspects that affect the deaf identity (in the purpose of psychological distress), we refer the concept of " identity suffering" discussed by Jaime Betts. In the Anthropological part, we present, also, fundamental considerations about the culture highlighting then in a dynamic perspective. As assumption of our reflections on what we understand as suppose of "identity suffering" to the deaf subjects (since the deaf are linguistic minorities , immersed in social contexts where most of people are listeners), we opted for the debate with Pierre Bourdieu, especifically in his essay about "the economics of linguistic exchanges", in which is located the language, also, as an essential factor to its interpretation about the possibility of linguistic domination. Finally, we present a brief analysis of public policies for the education of the deaf , whose function we want to highlight as the social integration of the deaf in his culture.